Exercise interventions to improve bone mineral density in athletes participating in low-impact sports: a scoping review - Anders Gulbrandsen Florvåg; Øyvind Angelshaug Berg; Ola Drange Røksund; Gøril Tvedten Jorem; Bård Erik Bogen (BMC Musculoskeletal Disorders)
Abstract Background Athletes participating in low-impact sports such as cycling and swimming are at increased risk for low bone mineral density, which may lead to long-term health issues. Exercise is known to increase bone mineral density, but there is little knowledge of the effects of this in athletes participating in low-impact sports. This review aims to identify potential exercise interventions that could improve bone health in these athletes. Methods There appears to be little research on this topic, and we addressed the research question using a scoping review to get a broad overview of the research literature. The scoping review was conducted following the methodological framework of Arksey and O´Malley. A literature search was conducted May 2024 in SPORTDiscus, Web of Science, Scopus, MEDLINE, EMBASE, Cinahl, Cochrane, and Google Scholar. The Consensus on Exercise Reporting Template was used to evaluate the reporting of the exercise intervention(s). Results A total of 2528 studies were screened and assessed for eligibility. Five studies met the inclusion criteria reporting results of exercise interventions on bone mineral density in cyclists and swimmers. Different designs were applied, and study populations varied. Five populations were explored; one cohort of adolescent swimmers (both sexes), one cohort of female Olympic artistic swimmers, one cohort of elite road cyclists (both sexes), one cohort of male competitive amateur cyclists, and one cohort of trained to well-trained cyclists (both sexes). Conclusion This scoping review found that resistance training, plyometric exercises, whole-body vibration, and a combined jumping exercise with collagen supplementation show promising results in improving bone mineral density in athletes participating in cycling and swimming. However, there is limited evidence due to few identified studies, with varying study designs and inconsistent exercise reporting, highlighting the need of further research to better understand how different training approaches can improve bone health in these athletes.